Improving quality of care for maternal and newborn health: a pre-post evaluation of the Safe Childbirth Checklist at a hospital in Bangladesh - Herfina Y. Nababan; Rubana Islam; Shabnam Mostari; Md Tariqujjaman; Malabika Sarker; Mohammad Tajul Islam; Corrina Moucheraud (BMC, 2017)
Abstract Background Bangladesh has achieved major gains in maternal and newborn survival, facility childbirth and skilled birth attendance between 1991 and 2010, but excess maternal mortality persists. High-quality maternal health care is necessary to address this burden. Implementation of WHO Safe Childbirth Checklist (SCC), whose items address the major causes of maternal deaths, is hypothesized to improve adherence of providers to essential childbirth practices. Method The SCC was adapted for the local context through expert consultation meetings, creating a total of 27 checklist items. This study was a pre-post evaluation of SCC implementation. Data were collected over 8 months at Magura District Hospital. We analysed 468 direct observations of birth (main analysis using 310 complete observations and sensitivity analysis with the additional 158 incomplete observations) from admission to discharge. The primary outcome of interest was the number of essential childbirth practices performed before compared to after SCC implementation. The change was assessed using adjusted Poisson regression models accounting for clustering by nurse-midwives. Result After checklist introduction, significant improvements were observed: on average, around 70% more of these safe childbirth practices were performed in the follow-up period compared to baseline (from 11 to 19 out of 27 practices). Substantial increases were seen in communication between nurse-midwives and mothers (counselling), and in management of complications (including rational use of medicines). In multivariable models that included characteristics of the mothers and of the nurse-midwives, the rate of delivering the essential childbirth practices was 1.71 times greater in the follow-up compared to baseline (95% CI 1.61-1.81). Conclusion Implementation of SCC has the potential to improve essential childbirth practice in resource-poor settings like Bangladesh. This study emphasizes the need for health system strengthening in order to achieve the full advantages of SCC implementation.